CONSUMER EXCISE TAXES: A HEAVY HIT ON WORKING FAMILIES (Tufts Archival Research Center, 2007)
Copy; Pamphlet on the consumer impact of excise taxes. Argues that workers have been disproportionately burdened by taxes in general. States that all excise taxes are regressive and particularly unfair for workers. Includes a graph showing wealth level and excise taxes paid.